School workers' knowledge, attitude and behaviour related to use of Toombak: a cross sectional study from Khartoum state, Sudan - Hatim Mohammed Almahdi; Anne Nordrehaug Åstrøm; Raouf Wahab Ali; Elwalid Fadul Nasir (BMC, 2017)
Abstract Background Toombak is a form of smokeless tobacco (SLT) that is locally made and consumed in Sudan and contains several carcinogenic elements. Use of Toombak has been etiologically linked to various oral diseases including oral cancer. This study aimed to obtain baseline information about the Toombak use among Sudanese school workers, as well as their knowledge about Toombak related health hazards and attitude towards their role in Toombak control. In addition, this study assessed the availability and effectiveness of control policies and preventive practices in the schools. Methods A cross-sectional school-based study using one-stage stratified random sampling procedure; four schools were selected randomly from each of seven localities. A total of 239 school workers' were recruited (census) from the selected schools in Khartoum State, Sudan. Results Of the school workers, 63% (147) were ≤40 years, half were females and 79.2% (187) were teachers. A total of 9.6% (22) school workers confirmed ever use of Toombak and the percentage of daily users amounted to 64.7% (11). Moreover, 76.2% (16) of ever Toombak users were ≥40 years and all of them were males (p < 0.001). Most of the school workers reported good knowledge, positive attitude towards their role in Toombak control and good preventive practice. Female school workers were more likely to report positive attitude towards their role in Toombak control (p < 05), and to report good knowledge. Those reporting good preventive practice in schools reported good knowledge more than two times than their counterpart (p < 0.001). Age was the strongest predictor of ever Toombak use among school workers (p < .001). Conclusions The use of Toombak among school workers was associated with poor knowledge, negative attitude towards their role in Toombak control and poor preventive practice, Therefore, school workers use of Toombak may reduce their motivation and use of their potential in the prevention of a major health problem caused by Toombak use and affects their role model behaviour. On the other hand, school workers engagement with preventive practices in schools' was associated with good knowledge which in turn empowers their positive attitude towards their role in Toombak control.